Diversity of Freshwater Shrimp in Toaya Village, Sindue District, Donggala Regency Based on Phenotypic Data - Risnawati Risnawati; I Made Budiarsa; Manap Trianto; I Nengah Kundera; Yulia Windarsih; Zulaikhah Dwi Jayanti (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Freshwater shrimp are aquatic resources that play important ecological and economic roles and exhibit considerable species diversity, characterized by variations in phenotypic traits. Information regarding the diversity of freshwater shrimp species and phenotypic variation in Toaya Village remains limited; consequently, data on the level of phenotypic diversity among species are still largely unavailable. This study aimed to identify the diversity of freshwater shrimp species and analyze their phenotypic characteristics, including morphometric and meristic traits, using a multivariate analytical approach. This research employed a descriptive-exploratory design with random sampling conducted across three observation stations. The collected freshwater shrimp specimens were identified based on morphological characteristics using established scientific literature as references and were subsequently measured using 40 phenotypic characters. The resulting data were analyzed using Principal Component Analysis (PCA) and the Unweighted Pair Group Method with Arithmetic Average (UPGMA). The results revealed the presence of four freshwater shrimp species, namely Macrobrachium mammilodactylus, Macrobrachium empulipke, Macrobrachium equidens, and Macrobrachium rosenbergii. These four species exhibited a phylogenetic relationship with a similarity coefficient of approximately 0.78. At the species level, individuals showed high phenotypic similarity (0.97–0.98), reflecting the consistency of phenotypic traits within each species. Principal Component Analysis demonstrated that the first two principal components accounted for the majority of phenotypic variation, with the greatest contributions originating from specific morphometric and meristic characters. This study concludes that the multivariate analytical approach applied was both effective and efficient in revealing diversity patterns based on phenotypic characteristics.